2014
DOI: 10.1093/nar/gku1148
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded DNA-dependent ATPase Irc3p is directly involved in mitochondrial genome maintenance

Abstract: Nucleic acid-dependent ATPases are involved in nearly all aspects of DNA and RNA metabolism. Previous studies have described a number of mitochondrial helicases. However, double-stranded DNA-dependent ATPases, including translocases or enzymes remodeling DNA-protein complexes, have not been identified in mitochondria of the yeast Saccharomyces cerevisae. Here, we demonstrate that Irc3p is a mitochondrial double-stranded DNA-dependent ATPase of the Superfamily II. In contrast to the other mitochondrial Superfam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 71 publications
3
41
0
Order By: Relevance
“…1c , irc3Δ). This result was similar to that previously observed with a different rho − strain a1184 23 . Furthermore, in the S1 treated a11 irc3 Δ mtDNA samples, we could also hardly visualize the regular Y and X structures ( Fig.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…1c , irc3Δ). This result was similar to that previously observed with a different rho − strain a1184 23 . Furthermore, in the S1 treated a11 irc3 Δ mtDNA samples, we could also hardly visualize the regular Y and X structures ( Fig.…”
Section: Resultssupporting
confidence: 92%
“…In accordance with our previous analysis, Irc3 did not unwind different linear DNA substrates with either 5′ or 3′ single-stranded extensions of 15–25 nt or with a 25 nt single-stranded fork structure at the end of a short double-stranded region ( Fig. 3a–c 23 ). However, preferential complex formation with branched DNA molecules and strong stimulation of Irc3 ATPase by the same cofactors suggested that Irc3 could unwind substrates resembling four-way Holliday junctions or replication forks.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations